Buku kedominikanan : SD kelas VI-semester 1&2 /Mg. Milke Sukarmi, Antoanet Murtiningsih ; editor, Sr. M. Serafine ; ilustrator, Tri Indriartanto, Gregorius Syarief, Thomas Sigit Budiawan - MILKE SUKARMI, MG.; Antoanet Murtiningsih; Serafine, Sr. M; Tri Indriartanto; Gregorius Syarief; Thomas Sigit Budiawan (St. Dominic Publishing, 2015)
viii, 62 hlm. : ilus. ; 24 cm.